HEMATOLOGY AND URINAL ANALYSIS PROFILE IN DIABETES MELLITUS - Rizka Ayu Wahyuni; Nurbidayah Nurbidayah; Nurul Amalia; Aulia Syafa Al Fitri; Noor Zahwa Mubarakah (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2025)
Type 2 Diabetes Mellitus (T2DM) constitutes a chronic metabolic disorder characterized by insulin resistance and consequential hyperglycemia. This state of elevated blood glucose can precipitate various complications, potentially influencing hematological parameters and urinary composition. This study aims to delineate the demographic characteristics, hematological profiles, and urinalysis results of individuals diagnosed with T2DM. Employing an observational descriptive design with a cross-sectional approach, the research examined T2DM patients who underwent laboratory testing at RSD Idaman Banjarbaru. The findings indicate that, from a total of 40 patients, the majority (n=18, 45%) belonged to the 46–55-year age cohort. Regarding gender distribution, female patients were more predominant, comprising 29 individuals (72.5%), compared to 11 male patients (27.5%). Most T2DM patients presented with hematological parameters within normal limits. However, specific hematological disturbances were still identified, notably reductions in Hemoglobin (Hb) and Mean Corpuscular Hemoglobin (MCH), alongside alterations in leukocyte differential counts. These anomalies may correlate with inflammatory complications or anemia prevalent in the T2DM population. Microscopic urinalysis revealed a high frequency of abnormalities across several parameters. Abnormal epithelial cells were observed in 26 patients (65%), aberrant erythrocytes in 28 patients (70%), and atypical leukocytes in 26 patients (65%). The most prevalent finding was abnormal urinary crystals, detected in 33 patients (82.5%). These results underscore the necessity for consistent renal health monitoring and proactive management in diabetic care. In conclusion, the hematological and urinalysis profiles of T2DM patients offer preliminary insights into their clinical status and the extent of associated complications, serving as valuable indicators for comprehensive patient management.